Lemongrass-Synthesized Silver Nanoparticles as Preservatives of Fermented Locust Beans - Saliu, Bolanle Kudirat; Agbabiaka, Tariq Oluwakunmi; Akolade, Jubril Olayinka (Indonesian Food and Nutrition Progress, 2024)
Fermented locust beans (FLB), produced from Parkia biglobosa (Mimosaceae-Fabaceae), are used in many parts of West Africa, including Nigeria, as condiments to enhance the taste and nutritional quality of foods. These benefits are, however, marred by the short shelf-life of FLB. Traditional preservative methods and the use of chemicals have their shortcomings. This study, therefore, investigated the effectiveness of lemongrass-synthesized silver nanoparticles (LSSNP) as a preservative of FLB. The LSSNP was prepared, characterized, and used to treat fresh FLB at 10% v/w. Dynamic light scattering analysis revealed a mean hydrodynamic size of 89 nm for the LSSNP, while transmission electron micrograph showed roughly spherical particles with an average size of 100 nm.  Bacillus licheniformis KGEB16, B. licheniformis APBSWPTB167, B. licheniformis PS4, B. subtilis CICC10148, and Enterobacter xiangfangensis M5S2B6 isolated were susceptible to LSSNP with comparable zones of inhibition to reference antibiotics. A significant reduction of the microbial load of FLB by up to 63.7% due to LSSNP treatment was achieved. The organoleptic and proximate properties of LSSNP-treated FLB were preserved. A histo-morphological study showed normal hepatic architecture in rats fed with LSSNP-treated FLB. This study showed that LSSNP possesses antimicrobial properties and can be employed as a green and safe alternative for the preservation of FLB.